1993
DOI: 10.1002/hep.1840180327
|View full text |Cite
|
Sign up to set email alerts
|

Fatty-acid metabolism and the pathogenesis of hepatocellular carcinoma: Review and hypothesis

Abstract: Despite increasing understanding of the genetic control of cell growth and the identification of several involved chemical and infectious factors, the pathogenesis of clinical and experimental hepatocellular carcinoma remains unknown. Available evidence is consistent with the possibility that selected changes in the hepatocellular metabolism of long-chain fatty acids may contribute significantly to this, process. Specifically, studies of the peroxisome proliferators, a diverse group of xenobiotics that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 107 publications
2
52
0
1
Order By: Relevance
“…Available evidence (Ockner et al, 1993) is consistent with the possibility that selected changes in the hepatocellular metabolism of long-chain fatty acids may contribute significantly to this process, nonneoplastic liver injury, and tumorigenesis in other tissues.…”
Section: Influence Of Liver Cancer On Fatty Acid Metabolismsupporting
confidence: 54%
See 1 more Smart Citation
“…Available evidence (Ockner et al, 1993) is consistent with the possibility that selected changes in the hepatocellular metabolism of long-chain fatty acids may contribute significantly to this process, nonneoplastic liver injury, and tumorigenesis in other tissues.…”
Section: Influence Of Liver Cancer On Fatty Acid Metabolismsupporting
confidence: 54%
“…Available evidence (Ockner et al, 1993) is consistent with the possibility that selected changes in the hepatocellular metabolism of long-chain fatty acids may contribute significantly to this process, which in turn leads to alterations in gene expression and in DNA itself. Moreover, certain intermediates of extramitochondrial fatty acid oxidation (e.g., the long-chain dicarboxylic fatty acids) impair mitochondrial function and are implicated as modulators of gene expression through their interaction with the peroxisome proliferator-activated receptor, which may also contribute to nonneoplastic liver injury and to tumorigenesis in other tissues.…”
Section: Influence Of Liver Cancer On Fatty Acid Metabolismmentioning
confidence: 55%
“…The anaerobic use of glucose as an energy source through glycolysis by the so-called 'Warburg effect' is a common feature of most tumors [22]. Moreover, cancer cell metabolism is also characterized by a low rate of fatty acid oxidation [22][23][24]. Although energy yield is low when substrates are not completely oxidized, these adaptations in rapidly growing cancer cells at the same time minimize ROS production and prevent DNA and proteins from being damaged by oxygen radicals when produced during oxidative phosphorylation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, decreased mitochondrial FA b-oxidation has been considered to be one of the major mechanisms underlying the disturbances in lipid metabolism in liver and steatosis (Ockner et al 1993). Furthermore, results from studies of both animal models and humans showed that decreased mitochondrial FA b-oxidation is closely associated with mitochondrial dysfunction (Nassir & Ibdah 2014).…”
mentioning
confidence: 99%